2018
DOI: 10.3390/catal8070286
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method to Encapsulate Laccase from Trametes versicolor with Enhanced Stability and Catalytic Activity

Abstract: In this work, laccase from Trametes versicolor pretreated with copper ion solution was entrapped in copper alginate beads. The presence of laccase in copper alginate beads was verified by Fourier transform infrared (FTIR) spectroscopy. The alginate concentration used was optimized based on the specific activity and immobilization yield. After entrapment, laccase presents perfect pH stability and thermal stability with 2,2′-azinobis-(3-ethylbenzthiazoline-6-sulphonate) (ABTS) as the substrate. Moreover, laccase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In contrast, both the completely dissociated HCl (pK a = −8.0) and the partially HC 2 O 4 − dissociated oxalate (pK a1 = 1.23; pK a2 = 4.9) inactivated laccase definitively at pH around 2.0 within 5-8 days of pre-incubation in the respective buffer solution (Section 3.3, Figure 3). Activity losses down to 3-9.5% are reported for Trametes versicolor and Pycnoporus cinnabarinus laccases incubated for 4-6 h in citrate and B&R buffer of pH 2.0 and 2.2, respectively [108,109], resembling the data of Figure 3. A 92 kDa laccase from the pH insensitive F. pinicola was stable from pH 1.5-11 [86].…”
Section: The Role Of Oxalatesupporting
confidence: 71%
“…In contrast, both the completely dissociated HCl (pK a = −8.0) and the partially HC 2 O 4 − dissociated oxalate (pK a1 = 1.23; pK a2 = 4.9) inactivated laccase definitively at pH around 2.0 within 5-8 days of pre-incubation in the respective buffer solution (Section 3.3, Figure 3). Activity losses down to 3-9.5% are reported for Trametes versicolor and Pycnoporus cinnabarinus laccases incubated for 4-6 h in citrate and B&R buffer of pH 2.0 and 2.2, respectively [108,109], resembling the data of Figure 3. A 92 kDa laccase from the pH insensitive F. pinicola was stable from pH 1.5-11 [86].…”
Section: The Role Of Oxalatesupporting
confidence: 71%
“…Thermal stability studies conducted between 20-60 • C showed that both laccase encapsulated in copper alginate beads and free laccase had their maximum activity at 40 • C. In addition, thermal stability was reduced between 40-60 • C, where the encapsulated laccase enzyme reduced at a lower rate than free laccase, indicating that immobilised laccase enzymes can withstand high temperatures. It was also reported that laccase encapsulated in copper alginate beadseliminated94.6%of 2,4-dichlorophenol, whereasfree laccase eliminated only 42.4%of the organic pollutant(2,4-dichlorophenol) in 10 h. Reusability analysis for laccase entrapped copper alginate beads revealed that elimination of 2,4-dichlorophenol was reduced from 94.6% to 80.4% in 10 cycles implying that this biocatalyst can be used for phenolic elimination in practical wastewater applications [70].…”
Section: Entrapment/encapsulationmentioning
confidence: 90%
“…Zhang et al (2018) encapsulated laccase from T. versicolor in copper alginate beads for the elimination of 2,4-dichlorophenol in contaminated water [70]. In encapsulation of laccase, sodium alginate solution (1.0% w/v) was added to a solution consisting of CuCl 2 and laccase.…”
Section: Entrapment/encapsulationmentioning
confidence: 99%
“…Microorganisms from activated sludge immobilized in alginate beads have been used to bioremediate 2-chlorophenol; this system was able to completely mineralize 2-chlorophenol (Sofer et al, 1990). In another study, 2,4-dichlorophenol degradation was carried out using Trametes versicolor laccase in copper alginate beads, which showed increased degradation rate by a factor of 2.4, and the specific activity of immobilized laccase was also found to be increased as compared to free enzyme (Zhang et al, 2018). Immobilization in alginate matrix is easy and low-cost method as well as provides good support and biocompatibility to the material being immobilized.…”
Section: Preparation Of Nanoemulsion-based Organogel Beads Of Agar An...mentioning
confidence: 99%